Travel survey of residents of Canada, type of expenditures, by visit duration - Statistics Canada (Government of Canada, 2018)
This table contains 264 series, with data for years 2011 - 2012 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography, province visited (11 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...), Type of expenditures (12 items: Total reallocated expenditures; Accommodation; Vehicle rental; Vehicle operation (including gas and repairs); ...), Visit duration (2 items: Total visits; Overnight visits).